Redesign of Administrative Violation Handling at Bawaslu Post Determination of Election Results: Redesain Penanganan Pelanggaran Administratif di Bawaslu Pasca Penetapan Hasil Pemilu - Supriyadi Supriyadi; Andi Intan Purnamasari (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The ideal election is an election whose process is good, qualified, and fair. Since the direct elections in 2014 until the simultaneous elections in 2019, election violations have often occurred, including election administration, election crimes, and the code of ethics of election organizers. The design of handling election administrative violations after the determination of the results: handling of the election administrative violations after the determination of election results, the original intense of Article 454 paragraph (6) and Article 461 paragraph (1) of the Election Law, and the ideal redesign in handling administrative violations in Bawaslu after the determination of election results. Research results: first, Bawaslu still receives election administrative reports after the determination of results. Second, the original intense of the norms limit the handling of election administrative violations to the process stage. Third, redesign the norms and the mechanism, then provide strict limits in the Constitutional Court Regulation.